Exercise and quality of life in medical students - Sattayanurak, Nisachol; Jirapornjaroen, Wichuda; Wisetborisut, Anawat; Jakkaew, Nalinee; Rojanasumapong, Auswin; Pinyopornpanish, Kanokporn (Biomedical Sciences and Clinical Medicine, 2018)
Objective To determine the prevalence of exercise among medical students and examine the association between exercise and quality of life (QOL). Methods A retrospective cross-sectional study was conducted using secondary health data from 2nd to 5th year medical student at Chiang Mai University (class of 2016). Adequate exercise was defi ned as an average exercise of 3 days/week with ≥30 minutes/session. QOL was assessed using SF-36. Results Of 933 medical students, 47.5% were male. Mean age was 21.5 years old. 29.3% had adequate exercise. There was no difference in levels of exercise among 2nd to 5th year. Male students were more likely to have adequate exercise than female (36.12% vs 23.06%, p <0.01). Medical students reported adequate exercise had better QOL compare to those who had inadequate exercise or no exercise (p <0.01). Conclusion Exercise is correlated with better QOL in medical students. However, majority of students have inadequate exercise. Encouraging medical students into exercise may improve their QOL during medical school. Further study should emphasize on types of exercise and factors associated with adequate exercise.